Infundibular dilations of the posterior communicating arteries: pathogenesis, anatomical variants, aneurysm formation, and subarachnoid hemorrhage. (18th June 2015) - Chen, Ching-Jen; Moosa, Shayan; Ding, Dale; Raper, Daniel M; Burke, Rebecca M; Lee, Cheng-Chia; Chivukula, Srinivas; Wang, Tony R; Starke, Robert M; Crowley, R Webster; Liu, Kenneth C
Abstract : Background: Cerebrovascular infundibular dilations (IDs) are triangular-shaped widenings less than 3 mm in diameter, which are most commonly found at the posterior communicating artery (PCoA). The aims of this systematic review are to elucidate the natural histories of IDs, determine their risk of progression to significant pathology, and discuss potential management options. Methods: A comprehensive literature search of PubMed was used to find all case reports and series relating to cerebral IDs. IDs were classified into three types: type I IDs do not exhibit morphological change over a long follow-up period, type II IDs evolve into saccular aneurysms, while type III IDs are those that result in subarachnoid hemorrhage without prior aneurysmal progression. Data were extracted from studies that demonstrated type II or III IDs. Results: We reviewed 16 cases of type II and seven cases of type III IDs. For type II IDs, 81.3% of patients were female with a median age at diagnosis of 38. All type II IDs were located at the PCoA without a clear predilection for sidedness. Median time to aneurysm progression was 7.5 years. For type III IDs there was no clear gender preponderance and the median age at diagnosis was 51. The PCoA was involved in 85.7% of cases, with 57.1% of IDs occurring on the left. Most patients were treated with clipping. Risk factors for aneurysm formation appear to be female gender, young age, left-sided localization, coexisting aneurysms, and hypertension. Conclusions: IDs can rarely progress to aneurysms or rupture. Young patients with type II or III IDs with coexisting aneurysms or hypertension may benefit from long-term imaging surveillance.